Benefits of Newborn Screening for Vitamin D-Dependant Rickets Type 1A in a Founder Population - Fortin, Carol-Ann; Girard, Lysanne; Bonenfant, Chloé; Leblanc, Josianne; Cruz-Marino, Tania; Blackburn, Marie-Eve; Desmeules, Mathieu; Bouchard, Luigi (Frontiers in Endocrinology, 2022)
Background Vitamin D-dependant rickets type 1A (VDDR1A) is a rare autosomal recessive disorder caused by pathogenic variants in the CYP27B1 gene. This gene is essential for vitamin D activation. Although VDDR1A is a rare condition worldwide, its prevalence is high in the Saguenay-Lac-Saint-Jean (SLSJ) region due to a founder effect. Daily intake of calcitriol before the onset of clinical manifestations can prevent them in affected children. Methods A genetic screening test was developed and validated for the CYP27B1 gene c.262del pathogenic variant. Newborn screening was implemented in the SLSJ region for this variant, and the feasibility and acceptability were assessed. Sixteen medical records of children affected with VDDR1A were reviewed to document the consequences of the disease at diagnosis. Results A total of 2000 newborns were tested for VDDR1A. Most families (96.5%) accepted the genetic test. We found a carrier rate of 1/29 for the c.262delG variant in our cohort, which is suggestive of a founder effect. We identified one child affected with VDDR1A and treatment was initiated before the onset of clinical manifestations. On average, children with VDDR1A were diagnosed at 13.8 ± 5 months of age, they had a significant failure to thrive at diagnosis, among other harmful health consequences. Conclusion Our study showed that in our population, the newborn genetic screening program is safe and feasible, it has high acceptability, and it is efficient to identify affected children. VDDR1A health consequences can be prevented by early initiation of treatment. Therefore, screening programs should be available for populations where it is deemed as beneficial from a public health perspective.